Inovasi Pembelajaran Berbasis Teknologi Digital untuk Meningkatkan Minat Belajar Anak Usia Dini: Studi Kasus di TK Yaa Bunayya Kota Bima - Aiman Putri; Ahmadin; Wahyu Mulyadin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Many educators still rely on conventional learning methods that are less engaging for children. In addition, limited access to technological devices and educational skills in utilizing technology are major obstacles in optimizing digital technology in early childhood learning. So this research aims to find out Digital Technology-Based Learning Innovations to Increase Early Childhood Learning Interest at Tk Yaa Bunayya, Bima City. This research will be conducted at Yaa Bunayya Kindergarten, Bima City, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study that digital technology-based learning innovations have a real positive impact on increasing children's interest in learning at Yaa Bunayya Kindergarten, Bima City. Digital technology applied in the form of learning videos, educational applications, interactive media, and other digital devices is able to create a learning atmosphere that is more fun, interesting, and motivates children to be actively involved in the learning process. The changes that can be seen significantly are the increase in children's activeness, enthusiasm, and interest in the material presented by the teacher.